(untitled) (Raparin Journal of Humanities (RJH), 2025)
The aim of this research is to evaluate the effects of a suggested strategy on the understanding of grammatical concepts in Kurdish grammar among eighth-grade elementary students, as well as their perceptions of the subject. To achieve this aim, an experimental design was employed that included both experimental and control groups. The research sample comprised 42 students. Following the alignment of variables (previous year’s Kurdish language subject grade, age, intelligence level, prior knowledge, and parental education level), participants were randomly assigned to two groups: an experimental group comprising 21 students instructed using the proposed strategy, and a control group of 21 students taught via traditional methods. The researcher subsequently developed a test for the acquisition of grammatical concepts comprising 25 multiple-choice items based on a specification table, and also created an attitude scale for the reading subject consisting of 35 items. The instruments were submitted to a panel of experts for validation. All test and attitude scale items received approval. To evaluate the reliability of the instruments, the (Test Re-Test) method was employed on a cohort of 88 students at the same academic level, conducted at two distinct intervals. The reliability coefficient for each measure exceeded 0.72. The research employed the following statistical tools: t-Test, Pearson correlation coefficient, Eta-square, Cohen’s (d) for effect size, and Chi-square (χ²). The study concluded that a statistically significant difference exists between the experimental and control groups, with the experimental group providing better outcomes in acquiring grammatical concepts and a more positive attitude toward the subject.